2015
DOI: 10.1016/j.ejpoleco.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Collective choice and individual action: Education policy and social mobility in England

Abstract: It is recognised that expressive preferences may play a major role in determining voting decisions because the low probability of being decisive in elections undermines standard instrumental reasoning. Expressive and instrumental preferences may deviate and in electoral settings it is more important to make policies expressively appealing. But policies are even more attractive if they can be made both expressively and instrumentally appealing. This paper studies education policy in England and proposes that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Likewise, Colclough and Al-Samarrai (2000) suggest that increased enrollment ratios in Sub-Saharan Africa and South Asia has often been achieved by lowering the "unit costs" of schooling. Studying education policy in current England, Jennings (2015) argues that also other education policies (such as banning private schools) may be supported by many voters on ethical (and sometimes instrumental) grounds, leading to "expressive voting" for such policies even if they induce sub-optimal education quality outcomes. Hence, there may even be negative effects of democracy on education quality due to the types of education policies that are electorally attractive.…”
Section: Democracy and Incentives To Improve Education Qualitymentioning
confidence: 99%
“…Likewise, Colclough and Al-Samarrai (2000) suggest that increased enrollment ratios in Sub-Saharan Africa and South Asia has often been achieved by lowering the "unit costs" of schooling. Studying education policy in current England, Jennings (2015) argues that also other education policies (such as banning private schools) may be supported by many voters on ethical (and sometimes instrumental) grounds, leading to "expressive voting" for such policies even if they induce sub-optimal education quality outcomes. Hence, there may even be negative effects of democracy on education quality due to the types of education policies that are electorally attractive.…”
Section: Democracy and Incentives To Improve Education Qualitymentioning
confidence: 99%
“…32 See the "inefficient unanimity" discussed by Brennan & Lomasky (1984). A recent example is Jennings (2015), who shows how an expressive preference for upward social mobility leads to an inefficient outcome in the British education system.…”
Section: Expressive Votingmentioning
confidence: 99%
“…The studies relevant to social-economic issues, including finance (Quamruzzaman et al 2014;Kim et al 2022;Jennings 2015), human resource development, (Zeng and Zhang 2022;Zakharia et al 2022;Sano and Tomoda 2010;Soemartono 2014;Hardy and Liu 2022); intergenerational education mobility (Guo et al 2019), income inequality (Nakamura 2015), quality basic education (Mirasol et al 2021), equity (Shi et al 2022), democracy (Yirci and Karaköse 2010), public education policy (Sano and Tomoda 2010), elite education (Koon 2022).…”
Section: Introductionmentioning
confidence: 99%
“…children's health, the relationship between the policy of the free primary school and the number of births, infant risk, and mortality. In the study of education policy in England and state spending on school education (Jennings 2015), the authors found that the regional distribution of students is geared towards middle-class families and that the allocation to schools by lottery may be accurate but not necessarily desirable. In addition, efforts to create a policy with ethical content to satisfy the correct priorities may be ineffective and deviate from the requirements of the policy.…”
Section: Introductionmentioning
confidence: 99%